Plan estratégico para la empresa “San Pablo de Tarugo” Cantón Chone período 2018-2022. - Chica Chica, María Selena (2018)
The objective of the research is to propose an applicable strategic plan that seeks to solve the need for a coherent direction, in such a way that it constitutes an essential documented tool, which is based on the strategic direction that the small company San Pablo de Tarugo wants to reach in the canton Chone, shaping the objectives, strategies, tactics, linking all those elements that are used in a specific period. Therefore, the first phase that sustains the research is the realization of a current situational diagnosis through the study of the internal and external environment that allowed the identification of positive and negative aspects, at the same time that changes were adapted to the mission and vision strategic; the second phase comprised the evaluation of environmental factors based on the application of matrices; consequently, in the third, the combined SWOT matrix was applied for the formulation of clear, solid and sustainable strategies. Finally, phase four involves the presentation of the strategic plan document that contains the main aspects of the object studied as well as the operative planning of each projected strategy. This research constitutes a predicted planning in a context of extended study that has as fundamental axes the business survival and the progressive growth.